Asymmetry within and around the human planum temporale is sexually dimorphic and influenced by genes involved in steroid hormone receptor activity. (January 2015) - Guadalupe, Tulio; Zwiers, Marcel P.; Wittfeld, Katharina; Teumer, Alexander; Vasquez, Alejandro Arias; Hoogman, Martine; Hagoort, Peter; Fernandez, Guillen; Buitelaar, Jan; van Bokhoven, Hans; Hegenscheid, Katrin; Völzke, Henry; et al.
Abstract: The genetic determinants of cerebral asymmetries are unknown. Sex differences in asymmetry of the planum temporale (PT), that overlaps Wernicke's classical language area, have been inconsistently reported. Meta-analysis of previous studies has suggested that publication bias established this sex difference in the literature. Using probabilistic definitions of cortical regions we screened over the cerebral cortex for sexual dimorphisms of asymmetry in 2337 healthy subjects, and found the PT to show the strongest sex-linked asymmetry of all regions, which was supported by two further datasets, and also by analysis with the FreeSurfer package that performs automated parcellation of cerebral cortical regions. We performed a genome-wide association scan (GWAS) meta-analysis of PT asymmetry in a pooled sample of 3095 subjects, followed by a candidate-driven approach which measured a significant enrichment of association in genes of the 'steroid hormone receptor activity' and 'steroid metabolic process' pathways. Variants in the genes and pathways identified may affect the role of the PT in language cognition.